Analisis Tindak Tutur Ekspresif dalam Film "Budi Pekerti" Karya Wregas Bhatuneja - Auliya Eka Wijayatri; Adinda Rizka Aulia Putri; Alif As-syifatul Azizah; Anita Fitriani; Weni Destrianti Zhaputri; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Tutik Wijayanti (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study is driven by the researcher’s interest in exploring the various forms of expressive speech acts that appear in the movie “Budi Pekerti.” The primary objective of this research is to identify the types of expressive speech acts performed by the characters in the film. Data were collected using observation and note-taking methods, specifically the free listening approach (simak bebas libat cakap, SBLC) and recording techniques. The analysis was conducted using a pragmatic framework, focusing on dialogue excerpts from the film’s characters. The findings reveal that the characters utilize seven types of expressive speech acts: expressing gratitude, giving praise, apologizing, criticizing, complaining, insinuating, and blaming. This study demonstrates that the expressive speech acts in “Budi Pekerti” are closely tied to the social and cultural context of the story. Each type of expressive speech act conveys functions and meanings that reflect the characters’ emotions and attitudes in specific situations. Overall, this research contributes to a better understanding of how expressive speech acts are used in film media and serves as a reference for future studies related to language use in diverse social and cultural contexts.